2022
DOI: 10.3390/ma15062307
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Nonwoven Inserts with Aerogel/PCMs for the Improvement of Thermophysiological Comfort in Protective Clothing against the Cold

Abstract: This study aimed to assess the developed nonwoven inserts with aerogel/PCM (phase change material) microcapsules for use in protective clothing against cold in terms of properties related to thermophysiological comfort. These inserts were obtained by the thermal bonding of a multilayer system consisting of needled-punched nonwovens and silica aerogel particles and/or PCM microcapsules evenly distributed between them. The influence of aerogel and PCM microcapsules on the basic physical properties of inserts, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…It is incredibly effective in the regions of the body that undergo compression, friction, and stress, including underfoot or insoles, the seat of the pants, knees, elbows, back, and chest. However, their serious disadvantage is their lack of breathability, not because of the aerogel but because of the membranes [100]. Future research will focus on the development of aerogel products with both thermal insulation properties and physiological comfort.…”
Section: Aerospacementioning
confidence: 99%
“…It is incredibly effective in the regions of the body that undergo compression, friction, and stress, including underfoot or insoles, the seat of the pants, knees, elbows, back, and chest. However, their serious disadvantage is their lack of breathability, not because of the aerogel but because of the membranes [100]. Future research will focus on the development of aerogel products with both thermal insulation properties and physiological comfort.…”
Section: Aerospacementioning
confidence: 99%
“…The impact of the aforementioned parameters of protective clothing on the firefighter’s comfort and safety is the subject of in-depth research [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. According to [ 3 ], the biophysical comfort properties of firefighters’ protective clothing can be improved with the incorporation of superabsorbent fibers into the inner fabric layer.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the critical impact of thermal liners in thermal protective performance for firefighter gear showed the positive influence of incorporating aerogel and microencapsulated phase change materials (PCMs) on thermal properties of protective clothing [ 5 ]. The use of aerogel and PCMs can also be an effective solution for improving the protective properties of various types of functional clothing and actively adapting its thermal insulation to the changing temperature conditions of the working environment [ 6 ]. Research [ 18 ] in which the influence of the thickness of the air gap on the thermal protection of protective clothing against hot steam and heat radiation showed that the air gap between clothing and skin is conducive and provides better thermal protection during exposure to heat radiation.…”
Section: Introductionmentioning
confidence: 99%
“…With the proposal of healthy, green and environmentally friendly lifestyles, outdoor sports have been highly sought after by the general public in recent years, which stimulates the market demand for sports/outdoors textiles to grow sharply [ 1 , 2 , 3 ]. In order to adapt to the complex and changeable environment of outdoor sports, scientists in academia have done tremendous work in recent years in studying the functional properties, such as waterproofness and breathability, cold resistance, heat preservation or UV protection of the sports/outdoors textiles [ 4 , 5 , 6 ]. Possessing the functional membranes as the core layer, waterproof and breathable fabric is the representative of the outdoor sports textile products.…”
Section: Introductionmentioning
confidence: 99%